(untitled) (Fiep Bulletin - online, 2020)
The objective of the research was to identify and analyze the understanding of the teachers of the Physical Education area, in the city of Campo Grande/MS, in relation to establishing criteria aiming at the evaluation of the learning of their students. study development: from what criteria do teachers develop learning assessment in physical education classes? The study was methodologically developed from exploratory, descriptive characteristics, with field research and subsequent qualitative analysis of the speeches of the interviewed subjects. Data collection was performed by applying a questionnaire to teachers during the continuing education process carried out by the municipal department of education in October 2017. 372 teachers were interviewed. The result of the investigation showed that most teachers evaluate their students based on criteria, involving motor, cognitive and affective partners. The study also showed that the evaluation process in Physical Education is one of the great challenges for teachers, due to its subjective character and specific ways of dealing with diversity, as well as the difficulties of objectively measuring students’ learning. It is suggested that teachers can evaluate students in their classes, defining criteria in the didactic referrals, and in line with the pedagogical proposal of the school, in order to clarify procedures that approach the appropriation of competences and skills aiming at qualitative aspects and above. all the promotion of learning in its multiple dimensions.